Analisis Standar Pelayanan Minimum Transjakarta Berdasarkan Observasi Dan Persepsi Penumpang - Muhamad Irfan Kresnadi; Dafa Arga Narendra; Nicholas Dwinovan (Jurnal Ilmiah Wahana Pendidikan, 2023)
As it is known that the provincial government of DKI Jakarta through Governor Regulation number 35 of 2014 has issued Minimum Service Standard (MSS) Transjakarta Busway Management unit. The Governor's Regulation should be the foundation for Transjakarta's operations and at the same time be a benchmark for the quality of PT. Transportation Jakarta. While Transjakarta service is still much complained by Transjakarta users. From the results of on-board survey conducted on 8 Transjakarta corridors shows the results that most of the measured parameters have been in accordance with MSS Transjakarta although there is variation between each corridor. However, based on the perception survey and passenger experience using questionnaires, it shows the low level of satisfaction of Transjakarta users to Transjakarta services especially in terms of waiting time and travel time. From these two survey results show the conflict between service standard and satisfaction level that makes the basis of analysis to Minimum Service Standards, whether the Minimum Service Standards that have been set too low or not and what matters can be a guide in determining Minimum Service Standards Transjakarta And other Public Transport.